2005
DOI: 10.1016/s0002-9440(10)62948-3
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Experimental Autoimmune Myocarditis Is Mediated by Interleukin-10-Producing T Cells that Are Controlled by Dendritic Cells

Abstract: Experimental autoimmune myocarditis (EAM) can be induced in the LewisMyocarditis is an inflammatory heart disease that can be initiated by infectious pathogens. 1-3 Dilated cardiomyopathy, which may follow myocarditis and represent the chronic stage of disease, is a major cause of heart failure and heart transplantation. 4 -6 Evidence suggests that autoimmune responses to cardiac antigens exposed after heart damage may play an important role in prolonged damage of myocardium. 3,7-9 Nevertheless, little progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 82 publications
0
41
0
Order By: Relevance
“…The role of these cytokines in ARF/RHD has been explored in other studies. In the animal model of ARF (cardiac myosin-induced autoimmune myocarditis and valvulitis in the Lewis rat), protection is conferred by IL-10-producing lymphocytes (17). In our study, a decrease in expression or the number of such lymphocytes may account for the decrease in measurable IL-10 expression.…”
Section: Discussionmentioning
confidence: 55%
“…The role of these cytokines in ARF/RHD has been explored in other studies. In the animal model of ARF (cardiac myosin-induced autoimmune myocarditis and valvulitis in the Lewis rat), protection is conferred by IL-10-producing lymphocytes (17). In our study, a decrease in expression or the number of such lymphocytes may account for the decrease in measurable IL-10 expression.…”
Section: Discussionmentioning
confidence: 55%
“…A low-dose CD28 mAb was sufficient to up-regulate the expression of Foxp3 and to promote the expansion of T regs , thus suppressing the function of CD4+CD25– T regs . In addition, the protection induced against EAM in Lewis rats arose from T cells regulated by increased IL-10 production by dendritic cells [25]. Moreover, some studies showed that the protection against autoimmune myocarditis using hepatocyte growth factor and the Chinese medicinal herb radix astragali was closely associated with the up-regulation of IL-10 [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of inflammatory heart disease models, IL-10 or IL-10 producing T cells protected against viral and experimental autoimmune myocarditis in mice [71,77,78]. Furthermore, anti-IL-10 antibody treatments prevented the development of heart specific tolerance against α-myosin/CFA immunization in mice [79].…”
Section: Development Of Therapeutic Strategies: Targeting Specific Cymentioning
confidence: 99%